Hydrolysis of ionic liquid–treated substrate with an Iocasia fonsfrigidae strain SP3-1 endoglucanase - Heng, Sobroney; Sutheeworapong, Sawannee; Wangnai, Chinnapong; Champreda, Verawat; Kosugi, Akihiko; Ratanakhanokchai, Khanok; Tachaapaikoon, Chakrit; Ceballos, Ruben Michael (Applied microbiology and biotechnology, 2024)
Recently, we reported the discovery of a novel endoglucanase of the glycoside hydrolase family 12 (GH12), designated IfCelS12A, from the haloalkaliphilic anaerobic bacterium Iocasia fonsfrigidae strain SP3-1, which was isolated from a hypersaline pond in the Samut Sakhon province of Thailand (ca. 2017). IfCelS12A exhibits high substrate specificity on carboxymethyl cellulose and amorphous cellulose but low substrate specificity on b-1,3;1,4-glucan. Unlike some endoglucanases of the GH12 family, IfCelS12A does not exhibit hydrolytic activity on crystalline cellulose (i.e., Avicel™). High-Pressure Liquid Chromatography (HPLC) and Thin Layer Chromatography (TLC) analyses of products resulting from IfCelS12-mediated hydrolysis indicate mode of action for this enzyme. Notably, IfCelS12A preferentially hydrolyzes cellotetraoses, cellopentaoses, and cellohexaoses with negligible activity on cellobiose or cellotriose. Kinetic analysis with cellopentaose and barely b- d -glucan as cellulosic substrates were conducted. On cellopentaose, IfCelS12A demonstrates a 16-fold increase in activity ( K M = 0.27 mM; k cat = 0.36 s −1 ; k cat /K M = 1.34 mM −1 s −1 ) compared to the enzymatic hydrolysis of barley b- d -glucan ( K M : 0.04 mM, k cat : 0.51 s −1 , k cat /K M = 0.08 mM −1 s −1 ). Moreover, IfCelS12A enzymatic efficacy is stable in hypersaline sodium chlorids (NaCl) solutions (up to 10% NaCl). Specifically, IfCel12A retains notable activity after 24 h at 2M NaCl (10% saline solution). IfCelS12A used as a cocktail component with other cellulolytic enzymes and in conjunction with mobile sequestration platform technology offers additional options for deconstruction of ionic liquid–pretreated cellulosic feedstock. Key points • IfCelS12A from an anaerobic alkaliphile Iocasia fronsfrigidae shows salt tolerance • IfCelS12A in cocktails with other enzymes efficiently degrades cellulosic biomass • IfCelS12A used with mobile enzyme sequestration platforms enhances hydrolysis